2016
DOI: 10.3892/ol.2016.5362
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA-17 functions as a prognostic biomarker in osteosarcoma

Abstract: MicroRNAs (miRNAs/miRs) are a class of small noncoding RNA molecules that have important roles in regulating the expression of target genes associated with the development and progression of cancer. The majority of miRNAs are expressed in a highly tissue- and region-specific manner, and released into the bloodstream as a consequences of different diseases. Furthermore, altered levels of miRNAs have been observed in several diseases, including cancer. In the present study, reverse transcription-quantitative pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…This demonstrated that certain miRNAs, including miR-33a, miR-150, miR-497 and miR-506, act as tumor suppressors ( 13 16 ). A number of previous studies have identified that miRNAs may serve as biomarkers for cancer risk stratification, outcome prediction, and even classification of the severity of the cancer ( 17 ). The identification of the miRNA molecule targets involved in tumor pathology may also provide insights into OS prognosis and facilitate the development of therapy for patients with OS ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrated that certain miRNAs, including miR-33a, miR-150, miR-497 and miR-506, act as tumor suppressors ( 13 16 ). A number of previous studies have identified that miRNAs may serve as biomarkers for cancer risk stratification, outcome prediction, and even classification of the severity of the cancer ( 17 ). The identification of the miRNA molecule targets involved in tumor pathology may also provide insights into OS prognosis and facilitate the development of therapy for patients with OS ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…OS is the most common primary malignant bone tumor. Studies suggest that this tumor is associated with increased levels of circulating miRNAs (including 14q32 miRNAs, miR-95-3p, miR-300, miR-101, miR-542-3p, miR-196a, miR-196b, and miR-491) and with decreased levels of miR-17, miR-497, miR-106a-5p, miR-16-5p, miR-20a-5p, miR-425-5p, miR-451a, miR-25-3p, and miR-139-5p [26][27][28][29][30][31]47,51,52]. Of these, serum miR-199a-5p concentrations are significantly higher in OS patients than in controls, and are significantly lower in post-operative samples than in preoperative samples [53].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular miRNAs are highly stable and easily detected in various biofluids, including whole blood, plasma, and serum [25,47]. Although circulating miRNAs are considered to be non-invasive biomarkers for cancer diagnosis and prognosis, the association between circulating miRNA profiles and those in tumor tissues remains unclear [26,48]. Many studies conducted to date have yielded inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Several other miRs, such as miR-21 and miR-17, are also expressed abnormally in the serum of patients with osteosarcoma. 30 , 31 Genome-wide microarray analysis might be an ideal way to identify circulating miRs with diagnostic ability, and a blood-based biomarker panel including more miRs and other molecular markers would help to improve the sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%